2013
DOI: 10.2139/ssrn.2306951
|View full text |Cite
|
Sign up to set email alerts
|

Crowding Out of Solidarity? – Public Health Insurance versus Informal Transfer Networks in Ghana

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…A growing literature deals with the consequences for informal support, i.e. monetary transfers provided by relatives, neighbors and friends, when insurance is introduced (Attanasio and Rios-Rull 2000;Hintz 2010;Landmann, Vollan, and Frölich 2012;Boucher and Delpierre 2014;Lin, Liu, and Meng 2014;Klohn and Strupat 2015). This literature investigates the extent of crowding out: if insurance crowds out informal support and delivers only incomplete risk coverage (for example, because not everybody gets insured, insurance does not fully compensate losses, or not all risks are insurable), introducing insurance does not necessarily lead to welfare improvements.…”
Section: Introductionmentioning
confidence: 99%
“…A growing literature deals with the consequences for informal support, i.e. monetary transfers provided by relatives, neighbors and friends, when insurance is introduced (Attanasio and Rios-Rull 2000;Hintz 2010;Landmann, Vollan, and Frölich 2012;Boucher and Delpierre 2014;Lin, Liu, and Meng 2014;Klohn and Strupat 2015). This literature investigates the extent of crowding out: if insurance crowds out informal support and delivers only incomplete risk coverage (for example, because not everybody gets insured, insurance does not fully compensate losses, or not all risks are insurable), introducing insurance does not necessarily lead to welfare improvements.…”
Section: Introductionmentioning
confidence: 99%
“…There is ambiguous evidence on whether expanded formal transfers weaken existing informal safety nets. In Ghana the introduction of a formal health insurance scheme appears to have crowded out informal transfers, due to a reduced willingness to contribute to transfer networks (Klohn and Strupat, 2013). Conversely, in urban Papua New Guinea workers living in traditional villages in urban areas (and so they stay embedded in the social relationships that sustain informal solidarity networks) do not opt out even when they have access to formal sources of insurance and other types of social protection (Boe- Gibson et al, 1998).…”
Section: Limited Understanding Of Complex Responses To Transfersmentioning
confidence: 99%
“…Contrariwise, other studies, mainly focusing broadly on social capital, have suggested that reciprocal support within social networks may facilitate insurance uptake by enabling individuals to afford the financial cost of scheme membership . Most studies are based on the reverse impact of formal health insurance on informal support, with the majority reporting a negative effect . Ligon et al explained that because formal health insurance provides an alternative protection against illness, it tends to reduce the social costs associated with nonparticipation in informal social protection systems.…”
Section: Introductionmentioning
confidence: 99%